Factors Affecting Patient Satisfaction And Revisit Intention At Beauty Clinic - Tasek, Brazelton; H.P. Tan, Pauline (Quantitative Economics and Management Studies, 2025)
This study aims to analyze the factors affecting patient satisfaction and their impact on revisit intention at Youtherna Beauty Clinic in Gading Serpong. This type of research based on its type is quantitative research with surveys . This study uses a survey with a cross-sectional study design based on the time of data collection, where data is collected once in a predetermined period of time. Data collected from October 2024 to November 2024 Data was collected through a questionnaire compiled on a likert scale that allowed respondents to rate the statements presented, such as in the form of the degree of approval or disapproval of the statements, which were then treated as ordinal data. The Likert scale facilitates the measurement of respondents' perceptions and attitudes in a more structured and measurable manner in the context of this study. Tangibility significantly influences both trust and customer perceived value (CPV), while empathy only affects CPV. Other service quality dimensions—reliability, responsiveness, and assurance show no significant effect. CPV positively affects customer satisfaction, which in turn significantly impacts both trust and revisit intention. Trust also significantly influences revisit intention. The model demonstrates moderate predictive accuracy for patient satisfaction (R² = 0.373) and revisit intention (R² = 0.364), indicating its adequacy in predicting patient revisit behavior at Youtherna Clinic.